Workplace happiness, well-being and their relationship with psychological capital: A study of Hungarian Teachers - Kun, Agota; Gadanecz, Peter (Current psychology (New Brunswick, N.J.), 2022)
Happiness and well-being at work has been an increasingly popular topic in the past two decades in academic and business contexts alike, along with positive psychology, through which organizations aim to find out, what makes working environments engaging and motivating. Few studies have focused on education, however, especially from a solution-focused perspective, even though it is a sector where employees are highly exposed to stress and burnout. Accordingly, the purpose of his study was to investigate the relationship between teachers’ psychological resources through the concept of psychological capital, workplace well-being and perceived workplace happiness. We used both qualitative (open-ended question) and quantitative (test battery) methods to examine the relation between the various factors. Content analysis of responses in our qualitative research suggests that the main pillars of teachers’ workplace happiness were realization of goals, feedback, finding meaning in work and social relationships. The results of our quantitative study indicated that workplace well-being and happiness correlated with inner psychological resources, hope and optimism in particular. We conclude that the future focus on employee well-being must take into account positive contributing factors and adopt a positively-oriented approach to promoting well-being. Suggestions for practical implications are also discussed.